Respuesta :

Answer:

According to diagram

[tex]\qquad{:}\longrightarrow\mathbb (7x-32)+(5x-27)=9x-8 [/tex]

  • Remove brackets

[tex]\qquad{:}\longrightarrow\mathbb 7x-32+5x-27 =9x-8 [/tex]

  • Simplify

[tex]\qquad{:}\longrightarrow\mathbb 7x-5x-32-27=9x-8 [/tex]

[tex]\qquad{:}\longrightarrow\mathbb 2x-59=9x-8 [/tex]

[tex]\qquad{:}\longrightarrow\mathbb 9x-8=2x-59 [/tex]

[tex]\qquad{:}\longrightarrow\mathbb 9x-2x=59+8 [/tex]

[tex]\qquad{:}\longrightarrow\mathbb 7x=67 [/tex]

[tex]\qquad{:}\longrightarrow\mathbb x=\dfrac {67}{7}[/tex]

[tex]\therefore\sf x=\dfrac {67}{7}[/tex]